Energy Intake of Men With Excess Weight During Normobaric Hypoxic Confinement - Mekjavic, Igor B.; Amon, Mojca; Simpson, Elizabeth J.; Kölegård, Roger; Eiken, Ola; Macdonald, Ian A. (Frontiers in Physiology, 2022)
Due to the observations of weight loss at high altitude, normobaric hypoxia has been considered as a method of weight loss in obese individuals. With this regard, the aim of the present study was to determine the effect of hypoxia per se on metabolism in overweight individuals. Eight overweight men (125.0±17.7 kg; 30.5±11.1 yrs, BMI: 37.6±6.2 kg·m-2) participated in a randomised cross-over study comprising two 10-day confinements: normobaric (altitude of facility ≃ 940 m) normoxia (NORMOXIA; PIO2=133 mmHg), and normobaric hypoxia (HYPOXIA; PIO2 was reduced from 105 to 98 mmHg over 10 days). Before, and at the end of each confinement, participants completed a meal tolerance test (MTT). Resting energy expenditure (REE), circulating glucose, GLP-1, insulin, catecholamines, ghrelin, peptide-YY (PYY), leptin, gastro-intestinal blood flow and appetite sensations were measured in fasted and postprandial states. Fasting REE increased after HYPOXIA (+358.0 ± 49.3 kcal·day-1, p = 0.03), but not after NORMOXIA (-33.1 ± 17.6 kcal·day-1). Postprandial REE was also significantly increased after HYPOXIA (p ≤ 0.05), as was the level of PYY. Furthermore, a tendency for decreased energy intake was concomitant with a significant body weight reduction after HYPOXIA (-0.7±0.2 kg) compared to NORMOXIA (+1.0±0.2 kg). The HYPOXIA trial increased the metabolic requirements, with a tendency towards decreased energy intake concomitant with increased PYY levels supporting the notion of a hypoxia-induced appetite inhibition, that could potentially lead to body weight reduction. The greater postprandial blood-glucose response following hypoxic confinement, suggests the potential development of insulin resistance.